A discriminação da mulher no mercado de trabalho: uma análise nos anos de 2002 e 2012 no estado do Ceará - Pimentel, Cynthia Paiva (2014)
This work focuses on analyzing the wage composition between genders in the state of Ceará in productive and non-productive attributes. From that point, measure the possibility of gender discrimination. We used data from the 2002 and 2012 PNAD - National Survey by Household Sampling for analysis of the last decade. And the data from Brazil and the Northeast were also collected for comparison with the data of Ceará. Were collected and analyzed the data by economic activity sectors, distributed as follows: sector 1: agriculture, sector 2: services, sector 3: industry, sector 4: public administration and sector 5: not defined activities. The Oaxaca-Blinder decomposition was used to determine how much of that wage gap is due to differences in productivity. Ceará was identified in 2002 that women earn less and have more years of education than men, thus signaling the possibility of discrimination. In 2012 the scenario has changed, women began to gain more and continued to have more years of education than men, indicating that there is no possibility of discrimination between genders. One has to consider the relevance of gender discrimination in Brazilian public policies insertion of more skilled workers, be they men or women. Thus, this work has an important role in view as is the overview of the wage gap for productive and non-productive attributes in the State of Ceará.